Profile of Disability in Leprosy Patients: A Retrospective Study - Geani, Silvani; Rahmadewi, Rahmadewi; Astindari, Astindari; Sawitri, Sawitri; Ervianti, Evy; Utomo, Budi; Cita Rosita Sigit Prakoeswa; Listiawan, Muhammad Yulianto (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2022)
Background: Leprosy is a chronic granulomatous infectious disease caused by Mycobacterium leprae that affects peripheral nerves and skin. The interaction between M. leprae and Schwann cells causes irreversible damage to peripheral nervous tissue afterward disability occurs. Involvement of the major nervous trunks of the extremities can produce sensory-motor deficits. The risk factors are delay in diagnosis, gender, age, type of leprosy, duration of disease, number of affected nerves, leprosy reaction, type of treatment, socioeconomic factors, education, ethnicity, and occupation. Purpose: The aim was to study the profile of leprosy patients with disability who seek treatment in Leprosy Division Dermatovenerology Outpatient Clinic RSUD Dr. Soetomo Surabaya. Methods: This was a descriptive retrospective study of leprosy patients with disability from January 2017 to December 2019. Result: The results of this study obtained a total of 275 leprosy patients with disabilities, which consisted of 76 patients (27.6%) with grade-1 disability and 199 patients (72.4%) with grade-2 disability. The majority were male (73.4%) and aged 25-44 years old (42.2%). Other dominant risk factors were MB type leprosy (92%), duration of disease more than 12 months (52.3%), no leprosy reaction (68%), and had received multidrug therapy (45.5%). Conclusion: Knowledge of disability risk factors can assist in improving management and education to prevent disability in leprosy patients.